Holistic Management Of A 35-Year-Old Woman With Breast Abscess Through A Family Medicine Approach - Sofia Tyasni Darma Perbasya; Tutik Ernawati (Jurnal EduHealth, 2024)
The aim of this study is to identify risk factors and clinical issues faced by patients, and to evaluate the implementation of family doctor services based on evidence-based medicine with a patient-centered, family-based, and community-oriented approach to improve care quality. This study used a case report design with a holistic approach to analyze the patient’s clinical condition and the role of family and environmental factors in recovery. Data collection included autoanamnesis (interviews with the patient), alloanamnesis (interviews with family members), physical examinations, diagnostic tests, and home visits. Data analysis combined qualitative methods to explore the context of health issues and family dynamics, with quantitative analysis to support findings from diagnostic tests. The approach aims to provide effective interventions for both the patient and their family, improving overall health quality. The research findings the mastitis experienced by the patient is closely linked to the patient's hygiene practices and personal habits, such as bathing every two days and frequently scratching areas around the breast folds. Additionally, a significant risk factor contributing to the condition is the frequent use of bras that do not fit properly. These factors combined have likely contributed to the development of mastitis. Furthermore, increasing the knowledge of the family members as a support system for the patient plays a crucial role in preventing the recurrence of the disease. When family members understand the patient's condition and necessary care measures, they can better assist in managing the illness and minimizing the risks.